Digital Pain Points: Analyzing Technology Barriers and Ai Companion Needs Among Micro-Enterprises In Jalan Tunjungan Surabaya - Desy Candra Novitasari; Wisma Miftahur Rozi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Purpose: This study investigates how heritage district constraints in Jalan Tunjungan, Surabaya, shape digital pain points and influence readiness for AI companion adoption among micro-enterprises, focusing on sales reporting and digital transformation barriers unique to historical commercial corridors.. Methods: Employing a sequential mixed-methods design, the research combined ethnographic observation (40 hours), semi-structured interviews with 20 micro-enterprise owners, and survey data from 35 businesses. Grounded in UTAUT2 and resource-based view theories, the study incorporated technology acceptance modeling within heritage business district contexts, utilizing methodological triangulation for validation. Results: Four primary pain points emerged: fragmented multi-platform management (78%), selective digital literacy gaps (65%), infrastructure limitations in heritage buildings (42%), and time-intensive manual reporting (87%). Paradoxically, 72% expressed AI assistance interest despite limited understanding. The study identified unique contextual barriers including heritage-infrastructure paradox and intergenerational digital deference within family businesses. Implications: The research proposes a contextualized AI companion framework addressing location-specific barriers and contributes to middle-range theory development in technology adoption. Practical recommendations include phased digital transformation strategies and hyper-localized implementation approaches for heritage commercial districts.